SELF EFFICACY IBU HAMIL TRIMESTER III DENGAN TINGKAT KECEMASAN DALAM MENGHADAPI PERSALINAN - Hikmah, Nurul (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
Hikmah, Nurul. 2018. The Relationship of Self Efficacy to the Pregnant Women Third Trimester with Anxiety Level in the Face of Labor in PMB Ngadillah, Asrikaton Village, Pakis. Essay. Applied Bachelor of Midwifery Studies Program, Health Polytechnic Ministry of Malang. Main advisor: Naimah, SKM., M.Kes. Counselor: Ita Yuliani, SST., M.Keb. Pregnancy is a physiological process that gives the changes in the mother physically and psychologically. Psychological changes that occur in the third trimester pregnant women one of them caused by anxiety before delivery. Prolonged anxiety can make a pregnant woman can not concentrate properly and loss of confidence. Self-efficacy in pregnant women is one of the psychological factors that predict the behavior of the mother and increase self-confidence and ability during pregnancy. Pregnant women who have a high self-efficacy can reduce the level of anxiety experienced. The purpose of this study to determine the relationship of self-efficacy third trimester pregnant women with the level of anxiety in the face of labor. The study design using analytic correlation with cross sectional approach. The study population throughout the third trimester pregnant women a number of 52 people with purposive sampling technique sampling. The research sample of 30 third trimester pregnant women in accordance with the inclusion criteria. The research instrument is questionnaire scale of confidence and Pregnancy Related Anxiety Questionnaire-Revised (PRAQ-R2). Results of research on self-efficacy is obtained 73.33% with moderate self efficacy, whereas for the anxiety level obtained 63.33% with mild anxiety. Data were analyzed using Spearman Rank ÃÂ values Ã¢â‚¬â€¹Ã¢â‚¬â€¹obtained value = 0.000 <ÃŽÂ± (0.05) with r = 0.651, H0 is rejected, which means there is a relationship of self-efficacy third trimester pregnant women with the level of anxiety in the face of labor with a strong correlation coefficient. The result is expected to be one way to improve self efficacy third trimester pregnant women in particular so that reduce anxiety before delivery. Keywords: Self Efficacy, Pregnant Women Third Trimester, Anxiety Level.